Incidence of Bacteremia After Endoscopic Variceal Ligation of Oesophageal Varices in Cirrhotic Patients (Medicine Today, 2013)
Bacteremia and infectious sequelea are frequent  complications after sclerotherapy. As cirrhotic patients are  immune deficient, bacteremia occurring as a consequence  of endoscopic variceal ligation (EVL) may develop systemic  infection. The aim of the study was to see the incidence of  bacteremia in cirrhotic patients after EVL.  In this study 91 cirrhotic patients with grade II-III  oesophageal varices were enrolled and 100 EVL sessions  were done. Patients receiving antibiotics, having evidence  of infection were excluded. After the completion of EVL,  blood samples for culture and sensitivity were collected at  5minute and after 30minute and subculture done in Blood  Agar and MacConkey Agar media. We followed the patients  for a week.  Of the one hundred cases there were 30 subjects in Child A,  48 in Child B and 13 in Child C class. Four patients (4%)  had positive blood culture after EVL, three of Child A class  and one of Child B class and non in Child C class. All three  patients of Child A had culture positive in their 30minute  sample and not in 5 minute sample. The Child B patient had  culture positive in his 5minute sample and not in 30minute  sample. The bacterium isolated was Coagulase negative  Staphylococcus, which we considered it as contaminant.  None of these patients developed any infectious sequelea.  The incidence of bacteremia after EVL is yet to be  ascertained. Post EVL antibiotic prophylaxis is not  recommended. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14109 Medicine TODAY Vol.24(1) 2012 pp.20-22